Percutaneous Coronary Intervention Using the DynamX Sirolimus-Eluting Bioadaptor: 12-Month Clinical and Imaging Outcomes - Mark Webster; Douglas Scott; Madhav Menon; Dougal McClean; Seif El-Jack; Gerard Wilkins; Scott A. Harding (Journal of Interventional Cardiology)
The DynamX Bioadaptor is a novel implant with uncaging elements that disengage after polymer resorption and permits restoration of vessel function, thereby potentially reducing late adverse cardiac events. We evaluated the safety and efficacy of this novel implant with imaging follow-up at 6-months, the time point when the bioadaptor starts to uncage. This prospective study enrolled 44 patients with up to two de novo lesions at seven centers in New Zealand treated with the DynamX Bioadaptor. Follow-up was planned out to 12-months. The primary safety and efficacy endpoints were 6-month target lesion failure (TLF) and late lumen loss. Patients presented with non-ST elevation myocardial infarction in 49%. Lesions (n = 45) were 16.0 ± 6.7 mm long, and 2.81 ± 0.41 mm in diameter. Device and procedure success were 100%, and acute lumen gain was 1.93 ± 0.35 mm. At 6-months, median in-device late lumen loss was 0.09 mm (IQR:0.05–0.16). Measured by intravascular ultrasound, the vessel, lumen, and device area remained constant. By optical coherence tomography, 96.4% ± 5.9% of struts per lesion were covered. Out to 12-months, no TLF and no definite or probable device thrombosis were reported. In conclusion, this study provides evidence of the safety and performance of the DynamX Bioadaptor with excellent 12-month clinical and 6-month imaging outcomes comparable to best-in-class drug-eluting stents (DES).